Effects of cryotherapy on joint position sense and intraarticular blood flow volume in healthy knee joints - Tsuneo Watanabe; Nobuo Terabayashi; Bateer Shi; Sohee Shin; Kosho Kasuga; Tamotsu Yabumoto; Katsuji Shimizu; Toshio Matsuoka (Japanese Society of Physical Fitness and Sports Medicine, 2013)
The purpose of this study was to investigate the influence of cryotherapy on knee joint position sense (JPS) and intraarticular blood flow volume (IBFV) and evaluate their relationships with cooling time as well as with surface temperature and deep temperature. Ten healthy volunteers were examined. This study consisted of a same-subjects repeated-measures design, with the timeframe of cryotherapy application (no therapy [resting control group], 2-min cooling, or 15-min cooling intervention) after exercise being the independent variable, and IBFV, knee JPS, surface temperature, and deep temperature serving as the dependent variables. Dependent variables were examined before 10-min cycle ergometer exercise (baseline), post-exercise, post-cooling, and 15 min later. In the 15-min cooling group, IBFV immediately after cooling and 15 min later were significantly lower than the post-exercise values (P = 0.048 and 0.016, respectively), and knee JPS at 15 min later was significantly lower than the baseline value (P = 0.037). By contrast, the 2-min cooling group showed no significant changes in either knee JPS or IBFV. Although both surface and deep temperatures after cooling were significantly lower than baseline (P = 0.034 and P < 0.001, respectively) in the 2-min cooling group, 15 min later they were significantly higher than post-cooling values (P = 0.023 and 0.023, respectively). These results suggest that 15-min cooling interventions functionally impair the sensitivity of JPS, although cooling is suitable for reduction of IBFV in deep tissue. Cooling interventions lasting less than 2-min did not affect knee JPS; however no reduction of IBFV occurred during this timeframe.